Photoresponsive transformation from spherical to nanotubular assemblies: anticancer drug delivery using macrocyclic cationic gemini amphiphiles. Issue 38 (21st April 2021) - Dey, Subhasis; Chatterjee, Soumya; Patel, Anjali; Pradhan, Nirmalya; Srivastava, Diship; Patra, Niladri; Bhattacharyya, Arindam; Manna, Debasis
Abstract : We developed NIR-light-responsive macrocyclic cationic gemini amphiphiles, one of which displayed various favorable properties of lipids, for example, stable spherical nanoaggregates and high phase transition temperature. Abstract : We developed NIR-light-responsive macrocyclic cationic gemini amphiphiles, one of which displayed various favorable properties of lipids. The NIR-light-mediated cleavage of the strained dioxacycloundecine ring led to the conversion of the spherical to a nanotubular self-assembly in the aqueous medium. This photo-mediated transformation from the spherical to nanotubular self-assembly resulted in the release of encapsulated hydrophobic anticancer drug molecule doxorubicin (Dox) in a controlled manner. The potent cationic gemini amphiphile also displayed lower cytotoxicity and efficient NIR-light-mediated Dox release efficacy to cancerous cells.